Sosialisasi Pentingnya Ilmu Politik Bagi Siswa Sma Sebagai Upaya Meningkatkan Kesadaran Demokrasi Dan Partisipasi Dalam Pemerintahan - Paul Adryani Moento; Eko Rachmat Saputro; Alexander Phuk Tjilen; Welhelmina Jeujanan; Hubertus Oja; Vinsenco Roberto Serano (Jurnal Transformasi Pendidikan Indonesia, 2025)
Political education is a crucial aspect of fostering democratic awareness and enhancing the active participation of young generations in governance. High school students, as future first-time voters, need to be equipped with a solid understanding of the political system, democracy, and their rights and responsibilities as citizens. This community service program aims to provide socialization on the importance of political science for high school students to increase their democratic awareness and participation in governmental processes. The methods used in this activity include lectures, interactive discussions, and a simple election simulation. The results show a significant improvement in students' understanding of political science, as well as an increased interest in active involvement in political activities within their school and community. Thus, this socialization program serves as a strategic step in fostering early political awareness among young generations.